Tribal development :past efforts and new challenges - Vays , N.N. (ed.) (Udaipur, 1989)
Tribal development is an area where some of our sensitive minds have been at work, where many adminis trators have made an impact, where there has been no dearth of ideas and suggestions for development. And yet the overall picture that emerges of the implementation of the accepted tribal policy and of the status of the tribal people, of their resources and of damage to their environment is dismal. The authors of the present work argue that though substantial benefits have accrued to tribal people over plan periods, the results have not been commensurate with expectations. There is, therefore no alternative to a rigorous evaluation of tribal policy and programmes to make sure that they reflect tribal people's needs and aspirations. The social change resulting from development has created some new problems. These problems are unhistorical for the tribals. In fact, these are the emerging challenges which the development administrator and social workers will have to face.
Keywords: Community development